2020
DOI: 10.5194/amt-13-6113-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sentinel-5P TROPOMI tropospheric NO<sub>2</sub> column densities with airborne and Pandora spectrometers near New York City and Long Island Sound

Abstract: Abstract. Airborne and ground-based Pandora spectrometer NO2 column measurements were collected during the 2018 Long Island Sound Tropospheric Ozone Study (LISTOS) in the New York City/Long Island Sound region, which coincided with early observations from the Sentinel-5P TROPOspheric Monitoring Instrument (TROPOMI) instrument. Both airborne- and ground-based measurements are used to evaluate the TROPOMI NO2 Tropospheric Vertical Column (TrVC) product v1.2 in this region, which has high spatial and temporal het… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 80 publications
8
75
0
1
Order By: Relevance
“…For this work, we rely on the operational TROPOMI NO 2 algorithm, which underestimates tropospheric vertical column NO 2 in urban areas. Previous studies suggest that this underestimate is due to the AMF and ∼5km pixel size which cannot resolve street-level variations in concentrations (Goldberg, Lu, Streets, et al, 2019;Griffin et al, 2019;Judd, Al-Saadi, Szykman, et al, 2020;Judd, Al-Saadi, Janz, et al, 2019;Zhao et al, 2020); investigating the effects of the AMF bias on trends as well as investigating the effects of the pixels sizes will be the subject of future work. Also, there may be a clear-sky bias (Geddes, Murphy, et al, 2012) that NO 2 column measurements are lower and incrementally more spatially homogeneous in the afternoon than during the morning (Chong et al, 2018;Fishman et al, 2008;Herman et al, 2019;Knepp et al, 2015;Penn & Holloway, 2020;Tzortziou et al, 2015); it is likely that data from geostationary platforms such as TEMPO (Zoogman et al, 2017), GEMS (W. J.…”
Section: Discussionmentioning
confidence: 99%
“…For this work, we rely on the operational TROPOMI NO 2 algorithm, which underestimates tropospheric vertical column NO 2 in urban areas. Previous studies suggest that this underestimate is due to the AMF and ∼5km pixel size which cannot resolve street-level variations in concentrations (Goldberg, Lu, Streets, et al, 2019;Griffin et al, 2019;Judd, Al-Saadi, Szykman, et al, 2020;Judd, Al-Saadi, Janz, et al, 2019;Zhao et al, 2020); investigating the effects of the AMF bias on trends as well as investigating the effects of the pixels sizes will be the subject of future work. Also, there may be a clear-sky bias (Geddes, Murphy, et al, 2012) that NO 2 column measurements are lower and incrementally more spatially homogeneous in the afternoon than during the morning (Chong et al, 2018;Fishman et al, 2008;Herman et al, 2019;Knepp et al, 2015;Penn & Holloway, 2020;Tzortziou et al, 2015); it is likely that data from geostationary platforms such as TEMPO (Zoogman et al, 2017), GEMS (W. J.…”
Section: Discussionmentioning
confidence: 99%
“…This is done based on the high-resolution APEX observations and under the assumption that the retrieved VCDs represent the true state of the NO 2 field. We have adopted a downsampling method described in Kim et al (2016) and Judd et al (2019): first, we construct a pseudo-TROPOMI VCD grid (VCD pTROPO ) by aggregating the APEX NO 2 VCDs (VCD APEX ) according to a weighted average technique within grid cells of 5 km × 5 km, 4.4 km × 4.4 km, and 1 km × 1 km. The pixels are square in shape in order to avoid an orientation bias.…”
Section: Downsampling Apex To Pseudo-tropomi No 2 Vcdsmentioning
confidence: 99%
“…Maximum differences can be up to ∼ 1900 % and are due to the overestimation of retrievals with very low background values in the original APEX data (∼ 0.3 × 10 15 molec cm −2 ). Based on a similar study applied to OMI data (13 km × 24 km) over the contiguous United States (Kim et al, 2016), it was found that under-or overestimation biases are on the order of 5-10 × 10 15 molec cm −2 or 20 %-30 % for major cities like Washington D.C. and New York. Biases are more than 100 % for small-scale cities like Norfolk and Richmond.…”
Section: Downsampling Apex To Pseudo-tropomi No 2 Vcdsmentioning
confidence: 99%
“…Other studies, comparing aircraft-and ground-based spectrometer measurements in urban and non-urban areas. have also found a systematic underestimation in TROPOMI NO 2 measurements, particularly during highly polluted conditions [34,[41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 86%